Inventarisasi Potensi Sumber Daya Uranium Daerah Kawat, Mahakam Hulu, Kalimantan Timur Tahapan Prospeksi Detil - Ngadenin, Ngadenin; Sukadana, I Gde; Muhammad, Adi Gunawan; Suripto, Suripto (EKSPLORIUM, 2011)
Result of the general prospecting in East Kalimantan has found several radioactivity outcrop anomalies at upper Mahakam in the acid volcanic rock area which is approximately 25 km2 in wide. The objective of the research is to know detailed geological information and characteristic of uranium mineralization. Method of this research are detailed geological, radiometric and geochemical mapping 1:10.000 on scale. The lithology of Kawat area is composed of seven units of rock. They are black clay unit, feldspatic sandstone unit, Nyaan rhyolite unit, lower andesite unit, Kawat rhyolite unit, upper andesite unit and tuffaceous sandstone unit. Evolving fault is dextral fault and normal fault. The trending of dextral fault is west-east and southwest-northeast, meanwhile the trending of normal faults is west-east and southwest - northeast. There are two period of uranium mineralization occurrences in the area, the first is connected with the eruption of Nyaan rhyolite magma and the second is connected with the eruption of Kawat rhyolite magma. Uranium mineralization occurred in the stage of hydrothermal process and including in the pneumatogenic class of volcanogenic uranium deposits. This investigation has yielded two sites of potential uranium sector are the Nyaan sector with an area of about 6 km2 and Kawat sector with an area of about 10 km2.